ANALISIS STRATEGI KOMUNIKASI PEMASARAN MELALUI FACEBOOK STUDI KASUS PRODUK PERAWATAN KULIT SKINTIFIC - Yusnaidi, Yusnaidi; Qadir, Abu Hassan Makmun Abdul; Devlishanti, Tio; Yuliana, Desi; Hasni, Jusnaini; Putri, Cut Mega; Mardaleta, Mardaleta (STAI Darul Qalam Tangerang, 2024)
This study aims to analyze marketing communication strategies used through the Facebook platform, focusing on case studies of Skintific skin care products. The research method used is qualitative analysis, which includes collecting data from the content of Skintific marketing communications on Facebook, as well as reviewing user responses and interactions to the content. The results of the analysis show various communication strategies used, including the use of visual content, keyword selection, and direct interaction with users. These findings provide deep insights into how marketing communication strategies can be optimized through social media platforms such as Facebook, particularly in the context of the skincare industry